A design and development of a web-based geospatial metadata system - Said, Mohamad Nor; Soon, Kean Huat (2001)
Increasing awareness within the GIS community of the need of an efficient spatial data management has sparked the idea of establishing a geospatial metadata database and developing a system that can support the access and maintenance of the database. A number of countries have already had such a system running but not in Malaysia yet even though the importance of it has been realized and some initial works are being made. This paper presents a research study on the design and development of a metadata management system that is accessible via World Wide Web (WWW). The system provides two main components, i.e. metadata entry tool and metadata access tool. The entry tool is developed for the data custodian who will be able to create and update their metadata and store them in a database. On the other hand, the access tool is for the GIS community to search for any desired metadata which can either be done by a textual or a spatial search. In order to meet these requirements, an application is developed using a combination of a number of packages including Microsoft Visual Basic 6.0 (with IIS application), Oracle, MapObject and MapObject Internet Map Server (MOIMS). The core metadata elements as decided by the Malaysian National Infrastructure For Land Information System (NaLIS) are adopted to be included in the database.